2023
DOI: 10.1021/acs.est.2c06985
|View full text |Cite
|
Sign up to set email alerts
|

Locked up Inside the Vessels: Rare Earth Elements Are Transferred and Stored in the Conductive Tissues of the Accumulating Fern Dryopteris erythrosora

Abstract: Rare earth elements (REEs) are strategic metals strongly involved in low-carbon energy conversion. However, these emerging contaminants are increasingly disseminated into ecosystems, raising concern regarding their toxicity. REE-accumulating plants are crucial subjects to better understand REE transfer to the trophic chain but are also promising phytoremediation tools. In this analysis, we deciphered REE accumulation sites in the REE-accumulating fern Dryopteris erythrosora by synchrotron X-ray μfluorescence (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…However, this may be problematic in many plant samples as co-localization of La-Ce-Sm-Gd occurs in D. erythrosora . 18 Note also that the information depth into the sample (absorption length of characteristic X-ray fluorescence) is different for L-shell and K-shell excitation. The extinction length in hydrated samples is 150 µm for L-lines, but in the centimeter range for K-lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this may be problematic in many plant samples as co-localization of La-Ce-Sm-Gd occurs in D. erythrosora . 18 Note also that the information depth into the sample (absorption length of characteristic X-ray fluorescence) is different for L-shell and K-shell excitation. The extinction length in hydrated samples is 150 µm for L-lines, but in the centimeter range for K-lines.…”
Section: Resultsmentioning
confidence: 99%
“… 17 Previously, we showed that it was possible to differentiate between REEs (La, Ce, Sm, Gd, Yb) in fronds of Dryopteris erythrosora , harboring a moderate/high accumulation of REEs (350 to 2000 mg kg −1 DW) but with relatively high concentrations of interfering elements (Fe, Mn). 18 Conversely, differentiation between La and Ce distribution was not possible in D. linearis samples with high prevailing concentrations of total REEs (tREEs) and interfering elements (Fe, Mn). 19 This is a consequence of the reliance on detectors [silicon drift detectors (SDDs) with an energy resolution 125 eV at 5.9 keV, increasing with count rate] that are typically not able to accurately determine the line intensities of the various REEs (due to their overlapping L-shell X-ray emission lines that are separated only by tens of eVs) in the presence of the K-lines of transition elements (such as Ti, Fe, Mn, Cr ).…”
Section: Introductionmentioning
confidence: 99%